2021
DOI: 10.1002/ajh.26384
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset hematological complications post COVID‐19: An emerging medical problem for the hematologist

Abstract: Coronavirus disease 19 (COVID‐19) is considered a multisystemic disease. Several studies have reported persistent symptoms or late‐onset complications after acute COVID‐19, including post‐COVID‐19 hematological disorders. COVID‐19‐induced coagulopathy, an immunothrombotic state, has been linked to thromboembolic and hemorrhagic events. Late‐onset thrombocytopenia related to immune system dysregulation has also been reported as a rare manifestation post COVID‐19. Close monitoring of laboratory dynamics is consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 76 publications
(105 reference statements)
0
35
0
1
Order By: Relevance
“…Long-COVID-19 emerges as a new aspect of the public health crisis triggered by the pandemic [32]. Delayed arterial thrombosis or venous thromboembolism post-COVID-19 is an emerging health problem [33][34][35]. The data presented herein allow to propose that evaluation of blood hypercoagulability (using D-dimer for instance) and endothelial cell activation could offer the possibility of prompt identification of COVID-19 survivors at risk of post-COVID-19 vascular complications.…”
Section: Discussionmentioning
confidence: 92%
“…Long-COVID-19 emerges as a new aspect of the public health crisis triggered by the pandemic [32]. Delayed arterial thrombosis or venous thromboembolism post-COVID-19 is an emerging health problem [33][34][35]. The data presented herein allow to propose that evaluation of blood hypercoagulability (using D-dimer for instance) and endothelial cell activation could offer the possibility of prompt identification of COVID-19 survivors at risk of post-COVID-19 vascular complications.…”
Section: Discussionmentioning
confidence: 92%
“…Korompoki et al. also summarized available evidence on post-acute COVID-19 hematological complications ( Korompoki et al., 2022 ). Overall, these studies have shown that persistent coagulation abnormalities and thrombosis are common in long covid.…”
Section: Long Covid Coagulation Abnormalitiesmentioning
confidence: 99%
“…Nevertheless, these impaired vascular endothelial cells often serve as the initial site of thrombosis. At this time, activated vascular endothelial cells are often overlooked, but they are the vulnerable basis of long COVID after discharge ( 31 , 33 , 39 , 43 ). Although vascular endothelial damage is difficult to distinguish clinically, it can be used as a differentiating point in pathology.…”
Section: Pulmonary Vulnerabilitymentioning
confidence: 99%
“…With the enhanced permeability of the alveolar membrane, the pulmonary edema causes further hypoxemia and deterioration ( 23 , 24 ). Pulmonary (micro)thrombus is key to severe hypoxemia, multiple organ dysfunction, and prolonged COVID-19 syndrome ( 25 33 ). Microthrombi can block microvessels in the alveolar capillaries, making it difficult for red blood cells to pass through.…”
Section: Introductionmentioning
confidence: 99%